Youth unemployment - Niall O'Higgins (Institute for the Study of Labor (IZA), 2015)
It's a pretty tough time to be a young European seeking to enter the labour market, but what exactly is the nature of the problem facing young people trying to find employment? It has long been recognized that unemployment is associated with a series of negative health consequences, both physical and psychological which tend to grow disproportionately with the duration of unemployment. Unemployment is also associated with unhappiness - both for those experiencing it as well as those who are employed but fear unemployment in a time of high job insecurity and it is widely understood that unhappiness is of itself linked to mental and physical ill-health. There is also a substantial body of evidence which links youth unemployment (and non-employment) to crime. Not only is crime costly for society it is also costly for the individual. Moreover, any such effects are likely to have long-term consequences; once a path of marginalization and criminality has been embarked upon, one's future prospects (and expectations) are likely to adjust accordingly. Thus, unemployment is bad for young people and for society as a whole; however, equally important, the detrimental consequences of youth unemployment are largely associated with longer term unemployment rather than unemployment per se. It is here that the really harmful effects of the recession have been felt by young people. During the recession, the prevalence of long-term unemployment amongst the young increased by more than one third. Moreover, this is not the only recent negative trend in young people's labour market experience with longer term consequences. In recent years, there has been increasing recognition that joblessness - or NEET - as it is now usually called, and not just unemployment per se is an issue for concern. Similarly, the emergence of high levels of temporary and part-time employment amongst young people and the longer term impacts of these contractual forms is also becoming a significant issue. This paper looks at recent trends in youth unemployment and joblessness and seeks to clarify some issues related to the nature of the youth labour market 'problem'.
Keywords: J13; J64; J81; I28; 330; youth labour markets; youth unemployment; NEET